In Search of Quality: Using Quality Matters to Analyze the Quality of Massive, Open, Online Courses (MOOCs) - Lowenthal, Patrick R.; Hodges, Charles B. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
The concept of the massive, open, online course (MOOC) is not new, but high-profile initiatives have moved MOOCs into the forefront of higher education news over the past few years. Members of institutions of higher education have mixed feelings about MOOCs, ranging from those who want to offer college credit for the successful completion of MOOCs to those who fear MOOCs are the end of the university as we know it. We set forth to investigate the quality of MOOCs by using the Quality Matters quality control framework. In this article, we present the results of our inquiry, with a specific focus on the implications the results have on day-to-day practice of designing online courses.